Quantitative determination of the boar taint compounds androstenone, skatole, indole, 3[alpha]-androstenol and 3[beta]-androstenol in wild boars (Sus scrofa) reveals extremely low levels of the tryptophan-related degradation products - Fischer, Jochen; Wuest, Matthias (Food chemistry, 2012)
The major boar taint compounds androstenone and skatole as well as the minor compounds indole, 3[alpha]-androstenol and 3[beta]-androstenol were determined in back fat samples of 23 male wild boars by applying a recently published SIDA-HS-SPME-GC/MS method. The boar pheromones androstenone, 3[alpha]-androstenol and 3[beta]-androstenol were found in extraordinary high concentrations, resulting in mean values of 3329 ng/g androstenone, 1273 ng/g 3[alpha]-androstenol and 545 ng/g 3[beta]-androstenol. Interestingly, skatole was not detectable in about 50% of the boars and negligibly low in all other samples as expressed by a mean skatole value of only 14 ng/g. Indole was also found in every sample, but again in low concentrations with a mean value of 40 ng/g. Possible factors explaining this remarkably low skatole deposition in wild boars such as intestinal flora and anatomy, dietary composition, housing or genetic predisposition are discussed in this paper.